-Efficacy of Stop Integrated Services in Controlling Tuberculosis (Tb) Cases in The Pasuruan City Area - Mokh. Sujarwadi; Mukhammad Toha; Ida Zuhroidah (Global Health Science Group, 2023)
One of the 2020-2024 National Medium-Term Development Plans (RPJMN) of the Ministry of Health is directed at increasing the control of Tuberculosis (TB). Several factors supporting the success of Tuberculosis (TB) treatment are a strong desire to recover. This motivation requires support from all components of health service providers in addition to family support. A friendly and uncomplicated healthcare environment provides comfort for patients. Innovation and modification of the health service model are needed, considering that treatment requires a relatively long time. One-door integrated health services are an alternative that needs to be implemented to achieve success in the treatment of Tuberculosis (TB). This research aims to describe one-stop integrated service innovation for Tuberculosis patients. Exploratory descriptive research design, purposive sampling technique, and a sample size of 50 respondents. The results of the study were all (100%) Tuberculosis patients came for treatment on time, no default cases were found (0%), all (100%) received fast service coverage in one place, all (100%) respondents were satisfied with the innovations provided, data normally distributed with p-value > 0.05. Friendliness of service can build trust between patients and staff, besides that service innovation is directed at providing convenience and speed in obtaining access to treatment so that it does not interfere with the patient's routine activities. One-stop integrated service is very effective in controlling tuberculosis cases. Innovations in the promotive and preventive fields are enhanced to prevent the addition of new cases.